A systematic review of medical students' and professionals' attitudes and knowledge regarding medical cannabis - Jared M. Weisman; Marcus Rodríguez (BMC, 2021)
Abstract Background Recently, the renewed global interest in cannabis' therapeutic properties has resulted in shifting attitudes and legislative policies worldwide. The aim of this systematic review is to explore the existing literature on medical professionals' and students' attitudes and knowledge regarding medicinal cannabis (MC) to assess any relevant and significant trends. Methods This systematic review was conducted in accordance with PRISMA guidelines. Using PubMed and Google Scholar, a literature search was performed to identify studies pertaining to healthcare professionals' and medical students' knowledge and attitudes regarding MC. There were no search limits on the year of publication; however, studies without primary data (e.g., abstracts, systematic reviews, meta-analyses) and non-English language papers were excluded. Studies were coded according to the following research questions: (1) Do respondents believe that cannabis should be legalized (for medicinal and/or recreational purposes)? (2) Are respondents confident in their level of knowledge regarding cannabis' clinical applications? (3) Are respondents convinced of cannabis' therapeutic potential? 4) What current gaps in knowledge exist, and how can the medical community become better informed about cannabis' therapeutic uses? and (5) Are there significant differences between the knowledge and opinions of healthcare students versus healthcare professionals with respect to any of the aforementioned queries? Chi-square tests were used to assess differences between medical students and medical professionals, and Pearson's bivariate correlations were used to analyze associations between survey responses and year of publication-as a proxy measurement to assess change over time. Results Out of the 741 items retrieved, 40 studies published between 1971 and 2019 were included in the final analyses. In an evaluation of 21 qualified studies (8016 respondents), 49.9% of all respondents favored legalization (SD = 25.7, range: 16-97%). A correlational analysis between the percentage of survey respondents who support MC legalization and year of publication suggests that both medical students' and professionals' support for MC legalization has increased from 1991 to 2019 (r(19) = .44, p = .045). Moreover, medical professionals favor the legalization of MC at a significantly higher rate than students (52% vs. 42%, respectively; χ 2 (1, N = 9019) = 50.72 p < .001). Also, respondents consistently report a strong desire for more education about MC and a substantial concern regarding MC's potential to cause dependence and addiction. Pearson's correlations between year of publication and survey responses for both of these queried variables suggest minimal changes within the last decade (2011-2019 for addiction and dependence, 2012-2019 for additional education; r(13) = − .10, p = .713 and r(12) = − .12, p = .678, respectively). Conclusion The finding that both medical students' and professionals' acceptance of MC has significantly increased in recent decades-in conjunction with their consistent, strong desire for more educational material-suggests that the medical community should prioritize the development of MC educational programs. MC is far more likely to succeed as a safe and viable therapy if the medical professionals who administer it are well-trained and confident regarding its clinical effects. Limitations include a lack of covariate-based analyses and the exclusion of studies published after the literature search was performed (June 2019). Future research should analyze studies published post-2019 to draw temporal comparisons and should investigate the effect of numerous covariates (e.g., gender, religiosity, prior cannabis use) as newer studies gather data on these factors [PROSPERO Registration: CRD42020204382].